The effect of body-weight and obesity bias on children’s self-esteem - Kornilaki, Ekaterina N. (Preschool and Primary Education, 2014)
The aims of this study were: a) to compare the self-esteem of obese children and normal–weight controls, and b) to examine whether obesity bias moderates the relationship between weight status and self-esteem. Fifty three normal-weight and forty 11-year-old obese children were administered Harter’s (1985) Self-Perception Profile for Children (SPPC), which consists of a global self-worth subscale and five domain-specific subscales that measure scholastic competence, social acceptance, athletic competence, physical appearance and behavioural conduct. To assess the strength of obesity bias, children were given an adjective attribution task embedded in the context of short vignettes. Obese children demonstrated lower social and athletic competence, physical appearance and global self-esteem compared to the normal-weight controls. Lower levels of obesity bias in obese children were associated with higher levels of esteem in physical appearance, athletic competence and global self-worth. The findings of the study show that low self-esteem is a psychological cost of childhood obesity, especially when combined with high obesity bias. This suggests that targeting obesity stigma can help obese children develop more positive self-perceptions.